Children's Character Education in Pandemic RA Raudhatul Hikmah Jombang (SCHOOLAR: Social and Literature Study in Education, 2022)
Speaking of character building, it is inseparable from how to shape the character of children from an early age starting from the family environment, school and community. However, of the three elements that are very influential in the formation of the character of the child is the family. For parents who are aware of the importance of children's education in the home, will see the child as a creature of reason who is growing up, passionate, and wants to investigate everything around him. That is also why parents need to feel called to educate their children since childhood in order to develop all the potential that is still buried in them